Das Internationale Theater. Bulletin der Internationalen Olympiade der Selbsttätigen Revolutionären Theater. Hrsg.: Internationaler revolutionärer Theaterbund
Engl. ed.: The international theatre. International union of the revolutionary theatre (ZO 16090). - French ed.: Le théâtre international. Bulletin ... (ZO 16089).